Novel genetic resources: Rice varieties for improving direct seeding genotypes - Anuson Thanasi; Samart Wanchana; Sureeporn Kate-ngam (Australian Journal of Crop Science, 2025)
Early seedling vigor is an essential characteristic for direct seeded rice. This study aimed to evaluate thirty-one rice varieties, categorized into three ecotypes (lowland, upland, and deep-wate cultivars), to identify traits associated with early seedling vigor under direct seeding conditions. Each evaluation was conducted using three biological replicates. The experiments comprised of tw parts: (a) deep-sowing tolerance and anaerobic germination tests and (b) aerobic germination conditions as a control. Early seedling vigor traits in rice, including mesocotyl length (MS), shoot lengt (SL), coleoptile length from deep-sowing experiment (COD), shoot weight (SW), coleoptile length from the anaerobic germination experiment (COA), coleoptile length under normal condition (CON), the anaerobic response index (AI), and seedling vigor (SV), were measured. The results demonstrated significant heritability across all traits. Principal component analysis identified CON and COD as the key variables influencing early seedling vigor traits. By using a multi-traits selection index, that considered eight important traits, U-19 (Plawng Aew), U-11 (Chum Phae 60), U-3 (Hawm Bao Rai), U-5 (Pin Gaew 56), and U-2 (Prachinburi 2) varieties were prioritized as important genetic resources for the enhancement of direct-seeding rice varieties. This research provide valuable insights into the traits associated with early seedling vigor. It is crucial for improving rice varieties that are widely adaptable to direct seeding conditions. The identified varieties showe promising for advancing breeding projects aimed at increasing the efficiency and sustainability of direct-seeding rice production systems.